Analysis of Optimal Health-Related Quality of Life Measures in Patients Waitlisted for Lung Transplantation. (5th March 2020) - Tokuno, Junko; Chen-Yoshikawa, Toyofumi F; Oga, Toru; Oto, Takahiro; Okawa, Tomoyo; Okada, Yoshinori; Akiba, Miki; Ikeda, Masaki; Nakajima, Daisuke; Hamaji, Masatsugu; Motoyama, Hideki; Aoyama, Akihiro; et al.
Abstract : Background . Improving health-related quality of life (HRQL) is an important goal of lung transplantation, and St. George's Respiratory Questionnaire (SGRQ) is frequently used for assessing HRQL in patients waitlisted for lung transplantation. We hypothesized that chronic respiratory failure (CRF)-specific HRQL measures would be more suitable than the SGRQ, considering the underlying disease and its severity in these patients. Methods . We prospectively collected physiological and patient-reported data (HRQL, dyspnea, and psychological status) of 199 patients newly registered in the waiting list of lung transplantation. CRF-specific HRQL measures of the Maugeri Respiratory Failure Questionnaire (MRF) and Severe Respiratory Insufficiency Questionnaire (SRI) were assessed in addition to the SGRQ. Results . Compared to the MRF-26 and SRI, the score distribution of the SGRQ was skewed toward the worse ends of the scale. All domains of the MRF-26 and SRI were significantly correlated with the SGRQ. Multiple regression analyses to investigate factors predicting each HRQL score indicated that dyspnea and psychological status accounted for 12% to 28% of the variance more significantly than physiological measures did. The MRF-26 Total and SRI Summary significantly worsened from the baseline to 1 year (p < 0.001 and p = 0.010, respectively) in 103 patients who underwent a follow-up assessment without lung transplantation, while the SGRQ showed a marginal significant worsening (p = 0.040 ). Conclusions . The MRF-26 and SRI are valid, discriminative, and responsive in patients waitlisted for lung transplantation. In terms of the score distribution and responsiveness, CRF-specific measures may function better in their HRQL assessment than the currently used measures do.